2002
DOI: 10.1136/jms.9.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity and screening for colorectal cancer

Abstract: The receipt of a screening test does not cause sustained anxiety and the existence of psychiatric morbidity is not a factor affecting a person's decision to accept or refuse a screening test for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 31 publications
4
61
0
Order By: Relevance
“…Existing studies of the psychological effects of CRC screening have shown few adverse effects of faecal occult blood testing, 103 FS 104 or colonoscopy 105 among the screened population as a whole. However, there has been little research looking at the psychological impact of entering a surveillance programme after screening.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies of the psychological effects of CRC screening have shown few adverse effects of faecal occult blood testing, 103 FS 104 or colonoscopy 105 among the screened population as a whole. However, there has been little research looking at the psychological impact of entering a surveillance programme after screening.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopy is invasive and may be annoying, both physically and psychologically [18,19]. On the other hand, it should be noted that faecal occult test has been associated with high anxiety in patients found with positive tests, requiring one month to return to normal level [18]; also many patients may develop psychic impairements due to their feeling affected with CRC while waiting for further exams [19] because of the high rate of false positive tests. As a consequence, performing a pancolonoscopy would contribute to reduce the anxietyrelated distress in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al measured anxiety scores in 100 individuals with false-positive results. Although the scores were highest after notification of the test result, they fell the day after colonoscopy and remained low 1 month later [13].…”
mentioning
confidence: 89%
“…Third, false-positive tests have the potential to generate anxiety, distress and depression symptoms, and changes in the overall perception of one's health status. As far as we know, only three studies have analyzed the psychological consequences of a false-positive result [11][12][13]. Parker et al measured anxiety scores in 100 individuals with false-positive results.…”
mentioning
confidence: 99%